Small bowel volvulus due to a large intestinal lipoma: A rare case report. (2020) - Buono, Giuseppe Di; Ricupati, Federica; Amato, Giuseppe; Gulotta, Leonardo; Romano, Giorgio; Agrusa, Antonino
Highlights: These are rare, benign, slow-growing mesenchymal tumors originating from adipose tissue in the bowel wall. Lipomas of mesentery, mesocolon, and antimesenteric side of intestine are extremely rare. We describe a case of small bowel obstruction secondary to volvulus due to an antimesenteric ileal lipoma. Mesenteric lipomas are rare clinical entity, with less than 50 cases described in English language literature. CT scan is the gold standard imaging modality for diagnosis of mesenteric lipoma and other lipomatous abdominal masses. It shows homogenous tumor of adipose tissue, gives information about features of the small bowel and if there is evidence of ischemia and can demonstrate the typical "vortix" pattern of a volvulus. Abstract: Introduction: A lipoma of the small bowel mesentery is a uncommon clinical entity. It rarely causes obstruction and volvulus of the small bowel. Case report: A 63 year old man was admitted to the emergency department with acute abdominal pain. Contrast-enhanced CT abdominal scan revealed small bowel obstruction due to a large fat density lesion suspected to be a lipoma. We performed a laparotomy in urgent setting that confirmed a small bowel volvulus secondary to a large antimesenteric lipoma. En-bloc resection with antiperistaltic side-to-side ileal anastomosis was done. Discussion: Mesenteric lipoma is rare. They are usually asymptomatic but when have large sizes can cause several symptoms related to small bowel obstruction or volvulus. The diagnosis is difficult and is rarely made prior to exploratory laparoscopy or laparotomy. CT scan is the gold-standard imaging technique. It can shows the typical characteristics of tumor and may demonstrate the typical "vortex" pattern of a volvulus. In patients with acute clinical presentation en-bloc resection of the lipoma with the affected small bowel loops is often necessary. This treatment may also be reserved in asymptomatic patients with large mesenteric lipomas to avoid future complications. Conclusion: Volvulus of the small bowel caused by an antimesenteric lipoma is a very rare entity. It is diagnosed by CT scan and surgery represents the standard treatment.